Social Capital Factors Supporting Rezita Meylani's Victory in the 2020 Indragiri Hulu Regent General Election - Agung Prasetyo Kanissha (International Journal of Economics Development Research (IJEDR), 2024)
Rezita Meylani is a Regent of Indragiri Hulu who broke the MURI record as the youngest regent in Indonesia history. Many people believe that her victory was influenced by her status as the wife of the former Regent of Indragiri Hulu for two terms, namely Yopi Arianto. Rezita is running as a candidate for Regent of Indragiri Hulu with her partner Drs.H. Junaidi Rachmat, M.Si in the 2020 Indragiri Hulu Regent General Election contestation was supported by three parties, namely Golkar, Nasdem, and Hanura. The vice-regent pair, Rezita Meylani – Junaidi Rachmat, won the Indragiri Hulu Regional Election with 50,412 votes or 26.5%, defeating the Rizal Zamzami – Yoghi Susilo pair supported by PKS and PKB with 50,232 votes or 26.4%. Therefore, the author conducted related research. Therefore, the author conducted research related to the social capital factors that supported Rezita Meylani's victory in the 2020 Indragiri Hulu Regent general election. The indicators for looking at the social capital applied in winning the regional head, especially by Rezita Meylani, are Trust. (trust), social networks, and social norms. In collecting data, this research uses qualitative methods by collecting primary data through in-depth interviews and triangulation with secondary data through literature review. Research findings show that the strong trust of the community is then mobilized effectively in political campaigns. Rezita Meylani's closeness to the community, which has been built over many years through interaction and active involvement in various social activities, has become a valuable asset in gaining voting support. This trust translates into real support on election day, where people who have benefited from Rezita Meylani's leadership so far cast their votes as a form of support and hope for the continuation of programs that have been running well.